Separating membrane and related secondary battery and electric device
Patent Information
- Application Number
- CN202380060584.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2023-04-10
- Publication Date
- 2025-03-25
AI Technical Summary
The existing secondary battery isolation membrane has insufficient ability to absorb and retain electrolyte, resulting in a low transmission rate of active ions, which limits the capacity retention rate and service life of the secondary battery.
An isolation membrane composed of a first porous base membrane, a second porous base membrane and a filler coating with a pore structure is used. The filler with a pore structure can physically adsorb electrolyte, improve liquid absorption and liquid retention capabilities, and pass through the pore structure Enhance the transmission rate of active ions and reduce resistance.
The capacity retention rate and service life of the secondary battery are significantly improved, the cycle performance is improved, and the mechanical properties and structural stability of the isolation film are enhanced.
Smart Images

Figure CN119698730A_ABST
Abstract
Description
Separator and related secondary battery and electrical device Technical Field
[0001] The present application relates to an isolation membrane and related secondary batteries and electrical devices. Background Art
[0002] Secondary batteries have the characteristics of high capacity and long life, and are therefore widely used in electronic devices such as mobile phones, laptops, electric vehicles, electric airplanes, electric boats, electric toy cars, electric toy boats, electric toy airplanes, and power tools, etc.
[0003] As the application scope of batteries becomes wider and wider, the requirements for the performance of secondary batteries are becoming increasingly stringent. For example, the capacity retention rate of secondary batteries still needs to be further improved.
[0004] Summary of the Invention
[0005] The present application is made in view of the above-mentioned problems, and its purpose is to provide a separator and its related secondary battery and electric device.
[0006] In a first aspect, the present application provides an isolation membrane, which includes a first porous base membrane, a second porous base membrane, and a coating layer. The coating layer is arranged between the first porous base membrane and the second porous base membrane, and the coating layer includes a filler with a pore structure.
[0007] Thus, the coating of the present embodiment includes a filler with a porous structure. The pores facilitate physical adsorption of electrolyte, storing the electrolyte within the pores, thereby improving the electrolyte absorption and retention capabilities. The porous structure also increases the transmission rate of active ions, effectively reducing resistance and improving the capacity retention rate of the secondary battery. A first porous base membrane and a second porous base membrane are provided on both sides of the coating. The first and second porous base membranes can impart excellent mechanical properties to the separator, improving the reliability of the secondary battery. The first porous base membrane and the second porous base membrane have the ability to absorb liquid themselves, which can further improve the liquid retention capacity; and since the coating is located between the first porous base membrane and the second porous base membrane, the first porous base membrane and the second porous base membrane form a coating effect on the coating, so that the liquid retention capacity of the coating can be further improved; furthermore, the first porous base membrane and the second porous base membrane can form a clamping and fixing effect on the coating, and the local area of the coating is not easy to fall off and separate from the porous base membrane. The distribution of the electrolyte in the isolation membrane is more uniform, and the transmission capacity of the active ions is more uniform, which is conducive to further improving the cycle performance of the secondary battery and improving the capacity retention rate.
[0008] In some embodiments, the average pore size of the filler's pore structure is denoted as D0, expressed in nm, with D0 ≥ 5; alternatively, 10 ≤ D0 ≤ 105. When the average pore size of the pore structure is within the above range, the filler exhibits a stronger attraction to the electrolyte, which improves the filler's ability to absorb and retain liquid, increases the capacity retention of the separator, and further enhances the transmission rate of active ions, effectively reducing resistance and extending the service life of the secondary battery.
[0009] In some embodiments, the porosity of the filler is denoted as P, and is 20% ≤ P ≤ 80%; alternatively, 20% ≤ P ≤ 70%; and further alternatively, 40% ≤ P ≤ 70%. When the porosity of the filler is within the above range, the volume of the filler's pore structure is relatively large, capable of storing a relatively large amount of electrolyte, improving the capacity retention of the separator, facilitating increased active ion transmission rate, reducing resistance, and extending the service life of the secondary battery. Furthermore, the volume of the filler's pore structure is relatively small, resulting in a high structural stability of the filler, which helps improve the overall structural strength of the separator.
[0010] In some embodiments, the specific surface area of the filler is denoted as S, and its unit is m 2 / g, 40≤S≤150; optionally, 60≤S≤120; further optionally, 60≤S≤80. When the specific surface area of the filler is within the above range, the outer surface of the filler has a larger contact area with the electrolyte, which facilitates the filler to absorb the electrolyte into the filler interior, improves the capacity retention rate of the separator, and can further increase the transmission rate of active ions, effectively reducing resistance and extending the service life of the secondary battery.
[0011] In some embodiments, the volume distribution particle size Dv50 of the filler is 0.01 μm to 3 μm, or optionally 0.05 μm to 2 μm. When the volume distribution particle size Dv50 of the filler is within the above range, it is more conducive to uniform dispersion of the filler in the coating.
[0012] In some embodiments, the porous filler comprises at least one of a metal-organic framework material and a mineral material.
[0013] In some embodiments, the metal-organic framework material includes one or more of a reticular metal-organic framework material, a zeolite imidazolate framework series material, a Lavahill framework series material, a pore-channel framework series material, a layered structure series material, and a zirconium-based three-dimensional microporous framework series material.
[0014] In some embodiments, the mineral material comprises one or more of halloysite nanotubes, vermiculite, attapulgite, sepiolite, montmorillonite, laponite, kaolinite, diatomaceous earth, and hydroxyapatite. Alternatively, the mineral material comprises a through-pore structure; further preferably, the mineral material comprises halloysite nanotubes.
[0015] In some embodiments, the pore structure of the filler includes at least one of a through-pore structure and a three-dimensional pore structure. Such a pore structure is conducive to further improving the liquid absorption and liquid retention capabilities of the isolation membrane.
[0016] In some embodiments, the thickness of the halloysite nanotube is H, in units of nm, 2≤H≤10; optionally, 2≤H≤5.
[0017] In some embodiments, the length of the halloysite nanotube is L, in μm, 0.05≤L≤2.50; optionally, 0.15≤L≤1.50.
[0018] Therefore, when the tube thickness and / or tube length of the halloysite nanotubes in the embodiment of the present application is within the above range, it is beneficial to further improve the liquid absorption and liquid retention capabilities of the halloysite nanotubes, improve the capacity retention rate of the isolation membrane, and is beneficial to the transmission performance of active ions, effectively reduce resistance, and increase the service life of the secondary battery.
[0019] In some embodiments, the filler content in the coating is greater than or equal to 10% and less than 100%, and may be 30% to 95%. When the filler content is within this range, the overall liquid absorption and retention capacity of the separator is improved, the capacity retention rate of the separator is increased, the transport performance of active ions is improved, the resistance is effectively reduced, and the service life of the secondary battery is increased.
[0020] In some embodiments, the thickness of the coating is W1, which is expressed in μm, and W1 ≥ 0.3; optionally, W1 ≥ 0.5; further optionally, 0.5 ≤ W1 ≤ 5.0.
[0021] In some embodiments, the coating further comprises a heat-resistant filler, and the porosity of the heat-resistant filler is optionally less than 15%, further optionally less than 10%, and further optionally less than 5%. The heat-resistant filler can improve the heat resistance of the separator.
[0022] In some embodiments, the coating further comprises a heat-resistant filler having an average pore size of less than or equal to 0.5 nm. The relatively small average pore size of the heat-resistant filler is beneficial for improving the mechanical strength of the heat-resistant filler and enhancing the overall mechanical properties of the separator.
[0023] In some embodiments, the mass percentage of the heat-resistant filler in the coating is denoted as A, and the mass percentage of the filler having a porous structure in the coating is denoted as B, then 0.1≤A / B≤10. Heat-resistant inorganic particles can further improve the heat resistance of the separator as a whole.
[0024] In some embodiments, the mass percentage of the heat-resistant filler in the coating is less than or equal to 85%.
[0025] In some embodiments, the heat-resistant filler includes at least one of inorganic particles and organic particles.
[0026] In some embodiments, the coating further comprises a binder; optionally, the binder comprises one or more of polyacrylate, acrylic acid, carboxymethyl cellulose, polyvinylidene fluoride-co-trichloroethylene copolymer, polymethyl methacrylate, polyvinyl pyrrolidone, polyvinyl acetate, polyethylene-co-vinyl acetate copolymer, polyethylene oxide, polyarylate, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, polyvinylidene fluoride, polyacrylonitrile, polyvinyl alcohol, starch, hydroxypropyl cellulose, regenerated cellulose, tetrafluoroethylene, polyethylene, polypropylene and cyanoethyl pullulan.
[0027] In some embodiments, the melting point of the first porous base membrane is less than or equal to the melting point of the second porous base membrane.
[0028] In some embodiments, the ratio of the average pore size of the first porous base membrane to the average pore size of the second porous base membrane is greater than 1, and can be optionally greater than or equal to 1.05.
[0029] In some embodiments, the average pore size of the first porous base membrane is 0.1 μm to 2 μm, and more preferably 0.1 μm to 0.5 μm.
[0030] In some embodiments, the average pore size of the second porous base membrane is 0.1 μm to 2 μm, and more preferably 0.1 μm to 0.35 μm.
[0031] In some embodiments, the porosity of the first porous base membrane is P1, the porosity of the second porous base membrane is P2, P1 / P2≥1.02; optionally, 1.05≤P1 / P2≤2.50.
[0032] In some embodiments, 30%≤P1≤80%; alternatively, 35%≤P1≤50%; and / or 25%≤P2≤70%; alternatively, 35%≤P2≤45%.
[0033] In some embodiments, the ratio of the thickness of the first porous base membrane to the thickness of the second porous base membrane is greater than or equal to 1.02; and can be optionally 1.2 to 5.0.
[0034] In some embodiments, the thickness of the first porous base membrane is 1 μm to 12 μm; optionally 3 μm to 6 μm.
[0035] In some embodiments, the thickness of the second porous base membrane is 2 μm to 12 μm; optionally 3 μm to 5 μm.
[0036] In some embodiments, the ion conductivity of the first porous base membrane is greater than the ion conductivity of the second porous base membrane.
[0037] In some embodiments, the ion conductivity of the first porous base membrane is 0.5 mS / cm to 1.5 mS / cm; optionally 0.7 mS / cm to 1.3 mS / cm.
[0038] In some embodiments, the ion conductivity of the second porous base membrane is 0.4 mS / cm to 1.5 mS / cm; optionally 0.6 mS / cm to 1.3 mS / cm.
[0039] In some embodiments, the liquid absorption rate of the isolation film is 80% to 180%, and optionally 100% to 170%.
[0040] A second aspect of the present application provides a secondary battery comprising the isolation membrane described in any embodiment of the first aspect of the present application.
[0041] A third aspect of the present application provides an electrical device comprising the secondary battery described in the second aspect of the present application. BRIEF DESCRIPTION OF THE DRAWINGS
[0042] In order to more clearly illustrate the technical solutions of the embodiments of the present application, the following briefly introduces the drawings required for use in the embodiments of the present application. Obviously, the drawings described below are only some examples of the embodiments of the present application. For ordinary technicians in this field, other drawings can be obtained based on the drawings without creative work.
[0043] FIG1 is a schematic diagram of one embodiment of a secondary battery according to an embodiment of the present application.
[0044] FIG. 2 is an exploded schematic diagram of an embodiment of the secondary battery of FIG. 1 .
[0045] FIG3 is a schematic diagram of a battery module according to an embodiment of the present application.
[0046] FIG4 is a schematic diagram of a battery pack according to an embodiment of the present application.
[0047] FIG. 5 is an exploded schematic diagram of the embodiment of the battery pack shown in FIG. 4 .
[0048] FIG6 is a schematic diagram of an embodiment of an electric device including the secondary battery according to the embodiment of the present application as a power source.
[0049] The drawings are not necessarily drawn to scale.
[0050] The reference numerals are as follows: 1. battery pack; 2. upper case; 3. lower case; 4. battery module; 5. secondary battery; 51. housing; 52. electrode assembly; 53. cover plate; 6. electrical device. DETAILED DESCRIPTION
[0051] The following detailed description specifically discloses embodiments of the separator of the present application, and its related secondary batteries and electrical devices. However, unnecessary detailed descriptions may be omitted. For example, detailed descriptions of well-known matters and repeated descriptions of substantially identical structures may be omitted. This is to avoid unnecessary length in the following description and to facilitate understanding by those skilled in the art. In addition, the drawings and the following description are provided to enable those skilled in the art to fully understand the present application and are not intended to limit the subject matter described in the claims.
[0052] " range " disclosed in the present application is limited in the form of lower limit and upper limit, and given range is limited by selecting a lower limit and an upper limit, and the selected lower limit and upper limit define the boundary of special range. The scope limited in this way can be to include end value or not include end value, and can be arbitrarily combined, that is, any lower limit can form a range with any upper limit combination. For example, if the scope of 60-120 and 80-110 is listed for specific parameters, it is understood that the scope of 60-110 and 80-120 is also expected. In addition, if the minimum range value 1 and 2 are listed, and if the maximum range value 3,4 and 5 are listed, then the following range can all be expected: 1-3, 1-4, 1-5, 2-3, 2-4 and 2-5. In this application, unless otherwise specified, the numerical range " ab " represents the abbreviation of any real number combination between a and b, wherein a and b are all real numbers. For example, a numerical range of "0-5" indicates that all real numbers between "0-5" are listed herein, and "0-5" is simply an abbreviation for these numerical combinations. Furthermore, when a parameter is expressed as an integer ≥ 2, this is equivalent to disclosing that the parameter is, for example, an integer of 2, 3, 4, 5, 6, 7, 8, 9, 10, 11, 12, etc.
[0053] Unless otherwise specified, all embodiments and optional embodiments of the present application can be combined with each other to form a new technical solution. Unless otherwise specified, all technical features and optional technical features of the present application can be combined with each other to form a new technical solution.
[0054] Unless otherwise specified, all steps of the present application may be performed sequentially or randomly, preferably sequentially. For example, a method includes steps (a) and (b), which indicates that the method may include steps (a) and (b) performed sequentially, or may include steps (b) and (a) performed sequentially. For example, a method may further include step (c), which indicates that step (c) may be added to the method in any order, for example, the method may include steps (a), (b), and (c), or may include steps (a), (c), and (b), or may include steps (c), (a), and (b), etc.
[0055] Unless otherwise specified, the terms "include" and "comprising" used in this application may be open-ended or closed-ended. For example, "include" and "comprising" may indicate that other components not listed may also be included or that only the listed components are included.
[0056] Unless otherwise specified, the term "or" is used in this application to be inclusive. For example, the phrase "A or B" means "A, B, or both A and B." More specifically, the condition "A or B" is satisfied if any of the following conditions are met: A is true (or exists) and B is false (or does not exist); A is false (or does not exist) and B is true (or exists); or both A and B are true (or exist).
[0057] In this application, the terms "first", "second", etc. are used for descriptive purposes only and should not be understood as indicating or implying relative importance.
[0058] In this application, the terms "plurality" and "multiple" refer to two or more.
[0059] Unless otherwise specified, the terms used in this application have the common meanings that are commonly understood by those skilled in the art.
[0060] Unless otherwise stated, the numerical values of the parameters mentioned in this application can be measured using various test methods commonly used in the art, for example, they can be measured according to the test methods given in the examples of this application.
[0061] A secondary battery consists of a positive electrode, a negative electrode, a separator, and an electrolyte. The separator is placed between the positive and negative electrodes to prevent short circuits between them while allowing active ions to pass freely through the electrolyte.
[0062] With the application and promotion of secondary batteries, people have higher and higher requirements for the performance (such as service life) of secondary batteries. The separator is an important component of secondary batteries, and the service life of secondary batteries can be extended by improving the performance of the separator.
[0063] Separators are typically polymer separators, but the low surface polarity of polymer separators results in poor electrolyte wettability. To improve separator wettability, related technologies often incorporate inorganic ceramic particles on the surface of polymer separators, hoping to enhance the overall electrolyte wettability of the separator. However, this approach only minimally improves the separator's ability to absorb and retain liquid. Consequently, during the secondary battery's charge and discharge process, electrolyte starvation limits the migration rate of active ions, severely deteriorating secondary battery performance, such as capacity retention.
[0064] In view of the above problems, the embodiment of the present application improves the isolation membrane, which includes a first porous base membrane and a second porous base membrane. The first porous base membrane and the second porous base membrane can give the isolation membrane excellent mechanical properties; a coating is arranged between the first porous base membrane and the second porous base membrane. Since the coating contains a filler with a porous structure, it is conducive to absorbing the electrolyte and can store the electrolyte inside the porous filler, thereby improving the liquid absorption and liquid retention capacity of the isolation membrane, and the pore structure of the porous filler can increase the transmission rate of active ions, effectively reduce resistance, and improve the capacity retention rate of the secondary battery.
[0065] Isolation film
[0066] In a first aspect, an embodiment of the present application provides a separator, which is applied to a secondary battery.
[0067] The isolation membrane includes a first porous base membrane, a second porous base membrane and a coating layer, wherein the coating layer is arranged between the first porous base membrane and the second porous base membrane, and the coating layer includes a filler having a pore structure.
[0068] The number of pore structures of the filler can be one or more. When the number of pore structures is one, the pore structure can be a straight pore that penetrates the filler itself, or a blind pore that does not penetrate the filler. When the number of pore structures is multiple, the pore structure can be pores that are parallel to each other or intersecting each other, and the pore sizes of the pores can be the same or different, and the shapes of the pores can be the same or different. Optionally, the pore diameter of the pore structure is a nanopore diameter, and the pore structure includes micropores, mesopores and macropores. Micropores refer to pores with a diameter of less than about 2 nm. Mesopores refer to pores with a diameter of about 2 nm to about 5 nm. Macropores refer to pores with a diameter greater than 50 nm.
[0069] The coating includes a filler with a porous structure. The pores are conducive to the physical adsorption of electrolyte and the electrolyte is stored in the pores, thereby improving the ability to absorb and retain the electrolyte. In addition, the pore structure of the porous filler can increase the transmission rate of active ions, effectively reduce resistance, and improve the capacity retention rate of the secondary battery.
[0070] A first porous base membrane and a second porous base membrane are arranged on both sides of the coating. The first porous base membrane and the second porous base membrane themselves have the ability to absorb liquid, which can further improve the liquid retention capacity; and since the coating is located between the first porous base membrane and the second porous base membrane, the first porous base membrane and the second porous base membrane form a coating effect on the coating, so that the liquid retention capacity of the coating can be further improved; furthermore, the first porous base membrane and the second porous base membrane can form a clamping and fixing effect on the coating, and the local area of the coating is not easy to fall off and separate from the porous base membrane. The distribution of the electrolyte in the isolation membrane is relatively uniform, and the transmission capacity of the active ions is relatively uniform, which is conducive to further improving the cycle performance of the secondary battery.
[0071] In some embodiments, the average pore size of the pore structure is recorded as D0, with the unit being nm, D0≥5; optionally, 5≤D0≤105; further optionally, 10≤D0≤105.
[0072] When the average pore size of the pore structure is within the above range, the filler has a strong attraction to the electrolyte, which is beneficial to improving the filler's ability to absorb and retain liquid, improving the capacity retention of the separator, and further improving the transmission rate of active ions, effectively reducing resistance, and extending the service life of the secondary battery. For example, the average pore size of the pore structure can be 5 nm, 8 nm, 10 nm, 15 nm, 20 nm, 25 nm, 28 nm, 30 nm, 35 nm, 40 nm, 45 nm, 50 nm, 55 nm, 60 nm, 65 nm, 70 nm, 75 nm, 80 nm, 90 nm, 100 nm, 105 nm, or a range consisting of any two of the above values.
[0073] In the embodiments of the present application, the average pore size of the filler has a well-known meaning in the art and can be tested using equipment and methods known in the art. For example, a BET nitrogen adsorption-desorption test can be used according to GB / T 19587-2017.
[0074] In some embodiments, the porosity of the filler is denoted as P, and 20%≤P≤80%. Alternatively, 20%≤P≤70%; further alternatively, 40%≤P≤70%.
[0075] When the porosity of the filler is within the above range, the volume of the filler's pore structure is relatively large, allowing it to store a relatively large amount of electrolyte, thereby improving the capacity retention of the separator, which in turn helps increase the transport rate of active ions, reduce resistance, and extend the service life of the secondary battery. Furthermore, the filler's pore structure is relatively small, resulting in high structural stability, which helps improve the overall structural strength of the separator. For example, the filler's porosity can be 20%, 30%, 40%, 50%, 60%, 70%, 80%, or a range consisting of any two of these values.
[0076] In the present application, porosity refers to the ratio of the filler's internal pore volume to the filler's total volume. Porosity can be measured using the gas displacement method according to GB / T 24586. Porosity (P%) = (L1 - L2) / L1 * 100%, where L1 is the apparent volume of the sample and L2 is the actual volume of the sample.
[0077] In some embodiments, the specific surface area of the filler is denoted as S, and its unit is m 2 / g, 40≤S≤150. Alternatively, 60≤S≤120; further optionally, 60≤S≤80.
[0078] When the specific surface area of the filler is within the above range, the outer surface of the filler has a larger contact area with the electrolyte, which is conducive to the filler absorbing the electrolyte into the filler, improving the capacity retention rate of the separator, and further improving the transmission rate of active ions, effectively reducing resistance and extending the service life of the secondary battery. For example, the specific surface area of the filler can be 40m 2 / g, 50m 2 / g, 60m 2 / g、70m 2 / g、80m 2 / g、100m 2 / g、110m 2 / g, 120m 2 / g, 130m 2 / g, 140m 2 / g, 150m 2 / g or a range consisting of any two of the above values.
[0079] In the embodiments of the present application, the specific surface area of a material is a well-known meaning in the art, and the surface area is usually expressed in m 2 The unit of % is expressed in g and can be measured using methods and instruments known in the art. For example, it can be measured using an inert gas (e.g., nitrogen) adsorption specific surface area analysis method according to GB / T 19587-2017 and calculated using the BET (Brunauer Emmett Teller) method. The nitrogen adsorption specific surface area analysis can be performed using a Tri-Star 3020 specific surface area pore size analyzer from Micromeritics, USA.
[0080] In some embodiments, the volume distribution particle size Dv50 of the filler is 0.01 μm to 3 μm; optionally 0.05 μm to 2 μm.
[0081] When the volume distribution particle size Dv50 of the filler is within the above range, it is more conducive to uniform dispersion of the filler in the coating. For example, the volume distribution particle size of the filler can be 0.01 μm, 0.02 μm, 0.03 μm, 0.05 μm, 0.10 μm, 0.12 μm, 0.15 μm, 0.20 μm, 0.30 μm, 0.50 μm, 0.60 μm, 0.80 μm, 1.00 μm, 1.20 μm, 1.50 μm, 1.80 μm, 2.00 μm, 2.50 μm, 2.80 μm, 3.00 μm, or a range consisting of any two of the above values.
[0082] In the embodiments of the present application, the Dv50 of the filler represents the particle size corresponding to the cumulative volume distribution percentage of the material reaching 50%, and can be measured using methods known in the art. For example, it can be measured using a laser particle size analyzer (such as the Malvern Master Size 3000) in accordance with the standard GB / T 19077.1-2016.
[0083] In some embodiments, the filler comprises at least one of a metal-organic framework material and a mineral material.
[0084] Exemplarily, metal-organic framework materials include one or more of isoreticular MOFs (IRMOFs), zeolite-imidazolate frameworks (ZIFs), Institute Lavoisier (MILs), pocket-channel frameworks (PCNs), coordinational pillared layers (CPLs), and zirconium-based three-dimensional microporous frameworks (UiOs). These materials have through-pore structures, which are beneficial for improving liquid absorption and retention capabilities.
[0085] Illustratively, the mineral material includes one or more of halloysite nanotubes, vermiculite (VRM), attapulgite (ATP), sepiolite (SEP), montmorillonite (MMT), laponite (LRD), kaolinite, diatomaceous earth (72% SiO2), and hydroxyapatite. Optionally, the mineral material includes halloysite nanotubes, which have a through-pore structure.
[0086] Vermiculite is a monoclinic layered silicate mineral with an ideal molecular formula of Mg 0.5 (H2O)4{Mg3[AlSi3O 10](OH)2}.
[0087] Attapulgite, also known as palygorskite, is a hydrous magnesium-aluminum silicate clay mineral with a chain-layered structure. Its ideal molecular formula is Mg5Si8O 20 (OH)2(OH2)4·4H2O.
[0088] Sepiolite is a fibrous hydrated magnesium silicate clay mineral with the ideal molecular formula of H8Mg2O. 10 Si3.
[0089] Montmorillonite is a layered mineral composed of hydrated aluminum silicate and is the main component of bentonite. Its ideal molecular formula is (Na, Ca) 0.33 (Al,Mg)2[Si4O 10 ](OH)2·nH2O.
[0090] Hectorite is a trioctahedral layered magnesium lithium silicate mineral with an ideal molecular formula of Li2Mg2O9Si3.
[0091] Kaolinite is a layered silicate mineral with the ideal molecular formula (Al4Si4O 10 (OH)8).
[0092] Diatomaceous earth is a siliceous rock whose main chemical component is silicon dioxide SiO2 (its percentage is more than 70%).
[0093] Halloysite nanotubes (HNTs) belong to silicate clay minerals with an ideal molecular formula of Al2Si2O5(OH)4·nH2O. They are inorganic nanotubes with high mechanical strength, good thermal stability, large specific area, strong dispersibility in polymers or water, and easy to disperse evenly in coatings.
[0094] Halloysite nanotubes have different compositions inside and outside the tubes. The inner wall of the tube is composed of Al-OH groups, while the outer surface is composed of Si-O-Si groups. HNTs carry positive and negative charges inside and outside the tube, respectively. The abundant hydroxyl groups on the inner wall of the tube form hydrogen bonds with small organic solvent molecules in the liquid electrolyte, effectively improving the liquid absorption capacity of the separator. The hollow tubular structure of halloysite nanotubes can store electrolyte, increasing the liquid retention capacity of the separator and improving the separator's capacity retention rate. This pore structure also improves the transport of active ions, effectively reducing resistance and extending the service life of the secondary battery.
[0095] In some embodiments, the thickness of the halloysite nanotubes is H, in nm, where 2≤H≤10; alternatively, 2≤H≤5. For example, the thickness of the halloysite nanotubes can be 2 nm, 3 nm, 5 nm, 7 nm, 8 nm, 9 nm, 10 nm, or a range consisting of any two of the aforementioned values.
[0096] In some embodiments, the length of the halloysite nanotubes is L, in μm, where 0.05 ≤ L ≤ 2.50; alternatively, 0.15 ≤ L ≤ 1.50. For example, the length of the halloysite nanotubes can be 0.05 μm, 0.10 μm, 0.15 μm, 0.20 μm, 0.25 μm, 0.30 μm, 0.50 μm, 0.60 μm, 0.80 μm, 1.00 μm, 1.20 μm, 1.30 μm, 1.50 μm, or a range consisting of any two of the foregoing values.
[0097] When the tube thickness and / or tube length of the halloysite nanotubes are within the above range, it is beneficial to further improve the liquid absorption and liquid retention capabilities of the halloysite nanotubes, improve the capacity retention rate of the isolation membrane, and be beneficial to the transmission performance of active ions, effectively reduce resistance, and increase the service life of the secondary battery.
[0098] In some embodiments, the halloysite nanotube itself is a hollow tubular structure, and the wall of the halloysite nanotube also has a pore structure. In other words, the pore structure of the halloysite nanotube includes two parts, one part is an internal hollow structure, and the other part is a pore structure on the wall. The structure of the halloysite nanotube is a combination of a through-hole structure and a three-dimensional pore structure, which can be more conducive to increasing the amount of electrolyte entering the halloysite nanotube and improving the liquid retention of the halloysite nanotube. In an embodiment of the present application, acid etching can be used to make the wall of the halloysite nanotube have a pore structure. Exemplarily, the halloysite nanotube is added to an acidic solution, stirred at 50°C to 80°C for 20min to 40min, and then the halloysite nanotube is washed to remove the acidic solution. After drying, the etched halloysite nanotube is obtained. In an embodiment of the present application, the acidic solution includes a mixture of hydrofluoric acid and other acid solutions in a ratio of 1:2. The other acid includes at least one of hydrochloric acid, sulfuric acid, nitric acid, etc., and hydrochloric acid can be selected.
[0099] For example, 30 g of halloysite nanotubes were weighed and added to 1 L of an acidic solution with a concentration of 1 mol / L, stirred at 70°C for 30 minutes, and then centrifuged and washed with deionized water until the pH of the supernatant was neutral. The solution was then placed in a vacuum oven at 100°C and dried for 2 hours to obtain the etched halloysite nanotubes.
[0100] In some embodiments, the pore structure of the filler may include a through-pore structure or a three-dimensional pore structure. A three-dimensional pore structure refers to a filler with parallel and / or intersecting pores. Through-pore structures or three-dimensional pore structures can further enhance the liquid absorption and retention capabilities of the separator, improving the capacity retention rate of the separator. A through-pore structure refers to pores that extend through the filler.
[0101] In some embodiments, the mass percentage of the filler in the coating is greater than or equal to 10% and less than 100%, and can be optionally 30% to 95%.
[0102] When the filler content by mass is within the above range, the overall liquid absorption and retention capacity of the separator can be improved, thereby increasing the separator's capacity retention rate, facilitating the transport of active ions, effectively reducing resistance, and extending the service life of the secondary battery. For example, the filler content by mass can be 10%, 20%, 30%, 40%, 50%, 60%, 70%, 80%, 90%, 95%, 96%, or a range consisting of any two of the above values.
[0103] In some embodiments, the thickness of the coating is W1, which is expressed in μm, and W1 ≥ 0.3; optionally, W1 ≥ 0.5; further optionally, 0.5 ≤ W1 ≤ 5.0.
[0104] When the coating thickness is within the above range, the amount of porous filler added is relatively high, which helps improve the separator's ability to absorb and retain liquid, improves the separator's capacity retention, improves the transport performance of active ions, effectively reduces resistance, and increases the service life of the secondary battery. For example, the coating thickness can be 0.3 μm, 0.4 μm, 0.5 μm, 0.8 μm, 1.0 μm, 1.2 μm, 1.5 μm, 2.0 μm, 3.0 μm, 4.0 μm, 5.0 μm, or a range consisting of any two of the above values.
[0105] In this application, the coating thickness has a meaning well known in the art and can be detected by equipment and methods well known in the art, for example, it can be tested by using a scanning electron microscope (such as ZEISS Sigma 300). As an example, the following steps can be followed: first, the isolation film containing the filler is cut into a sample to be tested of a certain size (for example, 6 mm × 6 mm), the sample to be tested is clamped with two conductive and heat-conductive thin sheets (such as copper foil), the sample to be tested and the thin sheets are glued and fixed with glue (such as double-sided tape), and a flat iron block of a certain mass (such as about 400 g) is used to press for a certain time (such as 1 hour) to make the gap between the sample to be tested and the copper foil as small as possible, and then the edges are trimmed with scissors and glued to a sample table with conductive glue, with the sample slightly protruding from the edge of the sample table. Then, place the sample stage into the sample holder and lock it securely. Turn on the power of the argon ion cross-section polisher (e.g., IB-19500CP) and evacuate the sample to a vacuum (e.g., 10 Pa to 4 Pa). Set the argon flow rate (e.g., 0.15 MPa), voltage (e.g., 8 kV), and polishing time (e.g., 2 hours). Adjust the sample stage to the rocking mode and start polishing. After polishing, use a scanning electron microscope (e.g., ZEISS Sigma 300) to obtain an ion polished cross-section morphology (CP) image of the sample to be tested.
[0106] In order to further improve the heat resistance of the isolation membrane, in some embodiments, the coating may further include a heat-resistant filler.
[0107] In some embodiments, the porosity of the heat-resistant filler is less than 15%; further, it can be less than 10%; further, it can be less than 5%; further, it can be less than or equal to 3%, and even the porosity of the heat-resistant filler can be 0%, which means that there is basically no porous structure inside the heat-resistant particles.
[0108] In some embodiments, the coating further includes a heat-resistant filler, and the average pore size of the heat-resistant filler is less than or equal to 0.5 nm. The average pore size of the heat-resistant filler is relatively small, which is beneficial to improving the mechanical strength of the heat-resistant filler and improving the overall mechanical properties of the isolation membrane. Moreover, the heat-resistant filler mainly plays a heat-resistant role, and has limited improvement on the liquid absorption and liquid retention capacity of the isolation membrane. Exemplarily, the average pore size of the heat-resistant filler can be 0, 0.1 nm, 0.2 nm, 0.3 nm, 0.4 nm, 0.5 nm or a range consisting of any two of the above values. An average pore size of 0 for the heat-resistant filler indicates that the heat-resistant filler is a solid structure with basically no pore structure.
[0109] In some embodiments, the mass percentage of the heat-resistant filler in the coating is recorded as A, and the mass percentage of the filler with a porous structure in the coating is recorded as B, then 0.1≤A / B≤10; when the isolation membrane meets the above range, it can take into account the improvement of the heat resistance and liquid retention capacity of the isolation membrane.
[0110] Illustratively, A / B may be 0.1, 0.2, 0.5, 0.8, 1.0, 1.2, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 4.5, 5.0, 5.5, 6, 6.5, 7, 8, 9, 10, or a range consisting of any two of the above values.
[0111] In some embodiments, the mass percentage of the heat-resistant filler in the coating is less than or equal to 85%; optionally, it is 30% to 65%.
[0112] Illustratively, the mass percentage of the heat-resistant filler can be 1%, 2%, 3%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 15%, 20%, 25%, 30%, 40%, 55%, 70%, 80%, 85% or a range consisting of any two of the above values.
[0113] In some embodiments, the heat-resistant filler includes at least one of inorganic particles and organic particles.
[0114] In some embodiments, the inorganic particles may include at least one of inorganic particles having a dielectric constant of 5 or higher, inorganic particles having the ability to transport active ions, and inorganic particles capable of electrochemical oxidation and reduction.
[0115] In some embodiments, inorganic particles having a dielectric constant of 5 or higher may include boehmite (γ-AlOOH), aluminum oxide (Al2O3), barium sulfate (BaSO4), magnesium oxide (MgO), magnesium hydroxide (Mg(OH)2), silicon oxide SiO x (0<x≤2), tin dioxide (SnO2), titanium oxide (TiO2), calcium oxide (CaO), zinc oxide (ZnO), zirconium oxide (ZrO2), yttrium oxide (Y2O3), nickel oxide (NiO), hafnium dioxide (HfO2), cerium oxide (CeO2), zirconium titanate (ZrTiO3), barium titanate (BaTiO3), magnesium fluoride (MgF2), Pb(Zr,Ti)O3 (abbreviated as PZT), Pb 1-m La m Zr 1-n Ti n O3 (abbreviated as PLZT, 0<m<1, 0<n<1) and Pb(Mg3Nb 2 / 3 ) at least one of O3-PbTiO3 (abbreviated as PMN-PT).
[0116] In some embodiments, the inorganic particles capable of transporting active ions may include lithium phosphate (Li3PO4), lithium titanium phosphate (Li x Ti y(PO4)3, 0<x<2, 0<y<3), lithium aluminum titanium phosphate (Li x Al y Ti z (PO4)3, 0<x<2, 0<y<1, 0<z<3), (LiAlTiP) x O y Glass-like (0<x<4, 0<y<13), lithium lanthanum titanate (Li x La y TiO3, 0<x<2, 0<y<3), lithium germanium thiophosphate (Li x Ge y P z S w , 0<x<4, 0<y<1, 0<z<1, 0<w<5), lithium nitride (Li x N y , 0<x<4, 0<y<2), SiS2 type glass (Li x Si y S z , 0<x<3, 0<y<2, 0<z<4) and P2S5 type glass (Li x P y S z , 0<x<3, 0<y<3, 0<z<7).
[0117] In some embodiments, the inorganic particles capable of electrochemical oxidation and reduction may include at least one of lithium-containing transition metal oxides, lithium-containing phosphates with an olivine structure, carbon-based materials, silicon-based materials, tin-based materials, and lithium titanium compounds.
[0118] In some embodiments, the ratio of the mass percentage of the heat-resistant filler in the coating to the mass percentage of the filler having a porous structure in the coating is 0.1 to 10.0; optionally 1.00 to 5.0.
[0119] When the addition amount of the heat-resistant filler and the porous structure is within the above range, the heat resistance of the separator and the ability to transport active ions can be improved, which is beneficial to further improve the service life of the secondary battery. For example, the ratio of the mass percentage of the heat-resistant filler in the coating to the mass percentage of the porous structure in the coating can be 0.1, 0.5, 1, 1.2, 1.5, 2.0, 2.5, 3.0, 3.5, 4.0, 5.0, 6.0, 7.0, 8.0, 9.0, 10, or a range consisting of any two of the above values.
[0120] In some embodiments, the organic particles may include at least one of polystyrene, polyethylene, polyimide, melamine resin, phenolic resin, polypropylene, polyester (e.g., polyethylene terephthalate, polyethylene naphthalate, polybutylene terephthalate), polyphenylene sulfide, polyaramid, polyamideimide, polyimide, copolymer of butyl acrylate and ethyl methacrylate, and mixtures thereof.
[0121] The coating in the embodiments of the present application may be a single-layer structure or a multi-layer structure. In some embodiments, the coating includes at least two sub-coatings, and the filler and the heat-resistant inorganic particles are arranged in different sub-coatings. Arranging the filler and the heat-resistant inorganic particles in different layers is conducive to the heat-resistant inorganic particles and the filler each playing their own role, thereby improving the heat resistance and liquid absorption and retention capabilities of the isolation membrane as a whole. In other embodiments, the coating includes at least two sub-coatings, and each sub-coating may include the filler and the heat-resistant inorganic particles.
[0122] In some embodiments, the coating includes a binder; optionally, the binder includes one or more of polyacrylate, acrylic acid, carboxymethyl cellulose, polyvinylidene fluoride-co-trichloroethylene copolymer, polymethyl methacrylate, polyvinyl pyrrolidone, polyvinyl acetate, polyethylene-co-vinyl acetate copolymer, polyethylene oxide, polyarylate, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, polyvinylidene fluoride, polyacrylonitrile, polyvinyl alcohol, starch, hydroxypropyl cellulose, regenerated cellulose, tetrafluoroethylene, polyethylene, polypropylene, and cyanoethyl pullulan.
[0123] The embodiments of the present application can improve the liquid retention capacity and mechanical properties of the isolation membrane by differentially setting the first porous base membrane and the second porous base membrane, which is beneficial to further improve the capacity retention rate of the secondary battery.
[0124] In some embodiments, the melting point of the first porous base membrane is less than or equal to the melting point of the second porous base membrane.
[0125] In some embodiments, the ratio of the average pore size of the first porous base membrane to the average pore size of the second porous base membrane is greater than 1, and can be greater than or equal to 1.05. For example, the ratio of the average pore size of the first porous base membrane to the average pore size of the second porous base membrane can be 1.01, 1.02, 1.05, 1.1, 1.5, 2.0, 3, 5, 10, or a range consisting of any two of the foregoing values.
[0126] In some embodiments, the average pore size of the first porous base membrane is 0.1 μm to 2 μm, and more preferably 0.1 μm to 0.5 μm.
[0127] In some embodiments, the average pore size of the second porous base membrane is 0.1 μm to 2 μm, and more preferably 0.1 μm to 0.35 μm.
[0128] In some embodiments, the porosity of the first porous base membrane is P1, the porosity of the second porous base membrane is P2, P1 / P2 ≥ 1.02; optionally, 1.05 ≤ P1 / P2 ≤ 2.50. When the porosity is within the above range, it can ensure that the air permeability of the base membrane is conducive to the migration of active ions, and because the porosity is relatively small, the mechanical properties of the base membrane can also be guaranteed, providing good support for the coating. For example, P1 / P2 can be 1.02, 1.03, 1.05, 1.50, 2.0, 2.50, or a range consisting of any two of the above values.
[0129] In some embodiments, 30%≤P1≤80%; alternatively, 35%≤P1≤50%. For example, the porosity of the first porous base membrane can be 30%, 35%, 40%, 45%, 50%, 60%, 70%, 80%, or a range consisting of any two of the above values.
[0130] In some embodiments, 25%≤P2≤70%; alternatively, 35%≤P2≤45%. For example, the porosity of the second porous base membrane can be 30%, 35%, 40%, 45%, 50%, 60%, 70%, or a range consisting of any two of the above values.
[0131] In some embodiments, the ratio of the thickness of the first porous base membrane to the thickness of the second porous base membrane is greater than or equal to 1.02; and can be optionally 1.2 to 5.0.
[0132] The above difference in thickness between the first and second porous base membranes leads to differences in their mechanical properties. The first porous base membrane has greater mechanical strength, which helps mitigate the risk of dendrites piercing the first porous base membrane. This allows the first porous base membrane to be positioned closer to the negative electrode, thereby improving the reliability of the secondary battery. For example, W2 / W3 can be 1.02, 1.05, 1.20, 1.50, 1.80, 2.00, 2.20, 2.30, 2.50, 3.00, 3.50, 4.00, 4.50, 5.00, or a range consisting of any two of these values.
[0133] In some embodiments, the thickness of the first porous base membrane is 1 μm to 12 μm, or optionally 3 μm to 6 μm. Specifically, the thickness of the first porous base membrane can be 1 μm, 2 μm, 3 μm, 5 μm, 6 μm, 8 μm, 10 μm, 11 μm, 12 μm, or a range consisting of any two of the above values.
[0134] In some embodiments, the thickness of the second porous base membrane is 2 μm to 12 μm; optionally 3 μm to 5 μm.
[0135] Specifically, the thickness of the second porous base membrane may be 2 μm, 2.5 μm, 3 μm, 4 μm, 5 μm, 6 μm, 8 μm, 10 μm, 11 μm, 12 μm, or a range consisting of any two of the above values.
[0136] In some embodiments, the ion conductivity of the first porous base membrane is greater than the ion conductivity of the second porous base membrane.
[0137] In some embodiments, the ion conductivity of the first porous base membrane is 0.5 MS / cm to 1.5 MS / cm; optionally 0.7 MS / cm to 1.3 MS / cm.
[0138] In some embodiments, the ion conductivity of the second porous base membrane is 0.4 MS / cm to 1.5 MS / cm; optionally 0.6 MS / cm to 1.3 MS / cm.
[0139] The embodiment of the present application has no particular restrictions on the material of the basement membrane. Any known basement membrane with good chemical stability and mechanical stability can be selected. For example, the first porous basement membrane and the second porous basement membrane can independently include at least one of a porous polyolefin-based resin membrane (such as polyethylene, polypropylene, polytetrafluoroethylene, polyvinyl fluoride, polyvinylidene fluoride), a porous glass fiber and a porous non-woven fabric. The first porous basement membrane and the second porous basement membrane can be independently selected from a single-layer film or a multi-layer composite film. When the first porous basement membrane is a multi-layer composite film, the materials of each layer can be the same or different. When the second porous basement membrane is a multi-layer composite film, the materials of each layer can be the same or different.
[0140] In some embodiments, the separator may further include an adhesive layer disposed between the coating and the base film (e.g., between the coating and the first porous base film, and / or between the coating and the second porous base film), wherein the adhesive layer includes a first binder. The adhesive layer not only prevents the coating from falling off, thereby improving the adhesion between the coating and the base film and the safety performance of the secondary battery, but also improves the interface between the separator and the electrode, thereby enhancing the cycle performance of the secondary battery.
[0141] Optionally, the first binder includes at least one of an acrylate monomer homopolymer or copolymer, an acrylic acid monomer homopolymer or copolymer, and a fluorine-containing olefin monomer homopolymer or copolymer. The comonomer includes, but is not limited to, at least one of the following: an acrylate monomer, an acrylic acid monomer, an olefin monomer, a halogen-containing olefin monomer, a fluoroether monomer, and the like.
[0142] Alternatively, the first binder includes a vinylidene fluoride based polymer, such as a homopolymer of vinylidene fluoride monomer (VDF) and / or a copolymer of vinylidene fluoride monomer and a comonomer. The comonomer may be at least one of an olefin monomer, a fluorine-containing olefin monomer, a chlorine-containing olefin monomer, an acrylate monomer, an acrylic monomer, and a fluoroether monomer. Alternatively, the comonomer may include at least one of trifluoroethylene (VF3), chlorotrifluoroethylene (CTFE), 1,2-difluoroethylene, tetrafluoroethylene (TFE), hexafluoropropylene (HFP), perfluoro (alkyl vinyl) ether (such as perfluoro (methyl vinyl) ether PMVE, perfluoro (ethyl vinyl) ether PEVE, perfluoro (propyl vinyl) ether PPVE), perfluoro (1,3-dioxole) and perfluoro (2,2-dimethyl-1,3-dioxole) (PDD).
[0143] In some embodiments, the liquid absorption rate of the isolation film is 80% to 180%. For example, the liquid absorption rate of the isolation film can be 80%, 90%, 100%, 120%, 130%, 140%, 150%, 160%, 170%, 180%, or a range consisting of any two of the above values.
[0144] In the embodiment of the present application, the test method of the liquid absorption rate of the isolation membrane is as follows: first, the isolation membrane is cut into a specified size (for example, 1 cm × 1 cm), and its mass m0 before being soaked in the electrolyte (the electrolyte can be a standard electrolyte, such as the electrolyte of the embodiment of the present application) is weighed; then the isolation membrane is soaked in the electrolyte for 24 hours and then taken out, the electrolyte on the surface of the isolation membrane is wiped off with a clean filter paper, and then its mass m1 is weighed; the liquid absorption of the isolation membrane is: W = m1-m0, and the calculation formula of the liquid absorption rate of the isolation membrane is:
[0145] Preparation method
[0146] In a second aspect, an embodiment of the present application provides a method for preparing an isolation membrane, which can be used to prepare the isolation membrane described in any embodiment of the first aspect of the present application.
[0147] The method comprises the following steps:
[0148] providing a first porous base membrane;
[0149] Disposing a coating layer containing a filler on the surface of the first porous base membrane, wherein the filler has a pore structure;
[0150] A second porous base membrane is arranged on the surface of the coating layer away from the first porous base membrane to prepare a separator.
[0151] In some embodiments, the coating layer may be formed by applying a coating slurry on the surface of the first porous base membrane and curing the coating slurry. The coating slurry may include a solvent, and the solvent may be water, such as deionized water.
[0152] In some embodiments, the coating slurry may further include other components, for example, a dispersant, a wetting agent, a binder, etc.
[0153] In some embodiments, the coating is performed using a coating machine. The present application embodiments do not particularly limit the type of coating machine; for example, a commercially available coating machine may be used. The coating machine includes a gravure roller; the gravure roller is used to transfer the slurry to the substrate.
[0154] In some embodiments, the coating method may be transfer coating, spin spray coating, dip coating, etc.
[0155] Some parameters such as raw materials and their contents used in the preparation method of the isolation membrane of the embodiment of the present application can refer to the isolation membrane of the first aspect of the embodiment of the present application, and will not be repeated here.
[0156] Unless otherwise specified, all raw materials used in the method for preparing the separator according to the embodiment of the present application can be obtained commercially.
[0157] secondary batteries
[0158] In a third aspect, an embodiment of the present application further provides a secondary battery.
[0159] Secondary batteries, also known as rechargeable batteries or storage batteries, are batteries that can be recharged after discharge to reactivate their active materials for continued use. Typically, a secondary battery comprises an electrode assembly and an electrolyte. The electrode assembly includes a positive electrode sheet, a negative electrode sheet, and a separator. The separator is positioned between the positive and negative electrodes to prevent short circuits between the positive and negative electrodes while allowing active ions to pass through.
[0160] The embodiments of the present application have no particular limitation on the type of secondary battery. For example, the secondary battery may be a lithium-ion battery, a sodium-ion battery, etc. In particular, the secondary battery may be a lithium-ion secondary battery.
[0161] The secondary battery described in the embodiment of the present application includes the isolation membrane described in any embodiment of the first aspect of the embodiment of the present application or the isolation membrane prepared by the method described in any embodiment of the second aspect of the embodiment of the present application, and the isolation membrane is arranged between the positive electrode plate and the negative electrode plate.
[0162] [Positive electrode]
[0163] In some embodiments, the positive electrode sheet includes a positive electrode current collector and a positive electrode film layer disposed on at least one surface of the positive electrode current collector and comprising a positive electrode active material. For example, the positive electrode current collector has two surfaces that oppose each other in its thickness direction, and the positive electrode film layer is disposed on either or both of the two opposing surfaces of the positive electrode current collector.
[0164] When the secondary battery of the embodiment of the present application is a lithium-ion battery, the positive electrode active material may include, but is not limited to, at least one of a lithium-containing transition metal oxide, a lithium-containing phosphate, and their respective modified compounds. Examples of the lithium transition metal oxide may include, but are not limited to, at least one of lithium cobalt oxide, lithium nickel oxide, lithium manganese oxide, lithium nickel cobalt oxide, lithium manganese cobalt oxide, lithium nickel manganese oxide, lithium nickel cobalt manganese oxide, lithium nickel cobalt aluminum oxide, and their respective modified compounds. Examples of the lithium-containing phosphate may include, but are not limited to, at least one of lithium iron phosphate, a composite material of lithium iron phosphate and carbon, lithium manganese phosphate, a composite material of lithium manganese phosphate and carbon, lithium iron manganese phosphate, a composite material of lithium iron manganese phosphate and carbon, and their respective modified compounds.
[0165] In some embodiments, in order to further improve the energy density of the secondary battery, the positive electrode active material for the lithium ion battery may include a general formula of Li a Ni b Co c M d O e A f At least one of a lithium transition metal oxide and a modified compound thereof. 0.8≤a≤1.2, 0.5≤b<1, 0<c<1, 0<d<1, 1≤e≤2, 0≤f≤1, M includes at least one of Mn, Al, Zr, Zn, Cu, Cr, Mg, Fe, V, Ti and B, and A includes at least one of N, F, S and Cl.
[0166] As an example, the positive active material for lithium ion batteries may include LiCoO2, LiNiO2, LiMnO2, LiMn2O4, LiNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2(NCM333),LiNi 0.5 Co 0.2 Mn 0.3 O2(NCM523), LiNi 0.6 Co 0.2 Mn 0.2 O2(NCM622),LiNi 0.8 Co 0.1 Mn 0.1 O2(NCM811), LiNi 0.85 Co0.15 Al 0.05 At least one of O2, LiFePO4, and LiMnPO4.
[0167] When the secondary battery of the embodiment of the present application is a sodium ion battery, the positive electrode active material may include but is not limited to at least one of sodium-containing transition metal oxides, polyanion materials (such as phosphates, fluorophosphates, pyrophosphates, sulfates, etc.), and Prussian blue materials.
[0168] As an example, the positive active material for sodium ion batteries may include NaFeO2, NaCoO2, NaCrO2, NaMnO2, NaNiO2, NaNi 1 / 2 Ti 1 / 2 O2、NaNi 1 / 2 Mn 1 / 2 O2、Na 2 / 3 Fe 1 / 3 Mn 2 / 3 O2、NaNi 1 / 3 Co 1 / 3 Mn 1 / 3 O2, NaFePO4, NaMnPO4, NaCoPO4, Prussian blue materials, general formula X p M' q (PO4) r O x Y 3-x At least one of the materials. p M' q (PO4) r O x Y 3-x , 0<p≤4, 0<q≤2, 1≤r≤3, 0≤x≤2, X includes H + 、Li + 、Na + , K + and NH4 + At least one of , M' is a transition metal cation, optionally at least one of V, Ti, Mn, Fe, Co, Ni, Cu and Zn, and Y is a halogen anion, optionally at least one of F, Cl and Br.
[0169] In the embodiment of the present application, the modified compound of each positive electrode active material may be a compound that performs doping modification and / or surface coating modification on the positive electrode active material.
[0170] In some embodiments, the positive electrode film layer may further optionally include a positive electrode conductive agent. The present application does not particularly limit the type of the positive electrode conductive agent. By way of example, the positive electrode conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, the mass percentage of the positive electrode conductive agent is ≤5% based on the total mass of the positive electrode film layer.
[0171] In some embodiments, the positive electrode film layer may further optionally include a positive electrode binder. The embodiments of the present application do not particularly limit the type of the positive electrode binder. As an example, the positive electrode binder may include at least one of polyvinylidene fluoride (PVDF), polytetrafluoroethylene (PTFE), vinylidene fluoride-tetrafluoroethylene-propylene terpolymer, vinylidene fluoride-hexafluoropropylene-tetrafluoroethylene terpolymer, tetrafluoroethylene-hexafluoropropylene copolymer, and fluorine-containing acrylic resin. In some embodiments, based on the total mass of the positive electrode film layer, the mass percentage of the positive electrode binder is ≤5%.
[0172] In some embodiments, the positive electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, aluminum foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include at least one of aluminum, aluminum alloy, nickel, nickel alloy, titanium, titanium alloy, silver, and silver alloy. As an example, the polymer material base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0173] The positive electrode film layer is typically formed by coating a positive electrode slurry onto a positive electrode current collector, drying, and cold pressing. The positive electrode slurry is typically formed by dispersing the positive electrode active material, an optional conductive agent, an optional binder, and any other components in a solvent and stirring them uniformly. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP).
[0174] [Negative electrode]
[0175] In some embodiments, the negative electrode sheet includes a negative electrode current collector and a negative electrode film layer disposed on at least one surface of the negative electrode current collector and comprising a negative electrode active material. For example, the negative electrode current collector has two opposing surfaces in its thickness direction, and the negative electrode film layer is disposed on either or both of the two opposing surfaces of the negative electrode current collector.
[0176] The negative electrode active material may be any negative electrode active material known in the art for use in secondary batteries. For example, the negative electrode active material may include, but is not limited to, at least one of natural graphite, artificial graphite, soft carbon, hard carbon, silicon-based materials, tin-based materials, and lithium titanate. The silicon-based material may include at least one of elemental silicon, silicon oxide, a silicon-carbon composite, a silicon-nitrogen composite, and a silicon alloy. The tin-based material may include at least one of elemental tin, tin oxide, and a tin alloy.
[0177] In some embodiments, the negative electrode film layer may further optionally include a negative electrode conductive agent. The present application does not particularly limit the type of the negative electrode conductive agent. By way of example, the negative electrode conductive agent may include at least one of superconducting carbon, conductive graphite, acetylene black, carbon black, Ketjen black, carbon dots, carbon nanotubes, graphene, and carbon nanofibers. In some embodiments, the mass percentage of the negative electrode conductive agent is ≤5% based on the total mass of the negative electrode film layer.
[0178] In some embodiments, the negative electrode film layer may further optionally include a negative electrode binder. The present application embodiment does not particularly limit the type of the negative electrode binder. As an example, the negative electrode binder may include at least one of styrene-butadiene rubber (SBR), water-soluble unsaturated resin SR-1B, water-based acrylic resin (e.g., polyacrylic acid PAA, polymethacrylic acid PMAA, sodium polyacrylate PAAS), polyacrylamide (PAM), polyvinyl alcohol (PVA), sodium alginate (SA), and carboxymethyl chitosan (CMCS). In some embodiments, the mass percentage of the negative electrode binder based on the total mass of the negative electrode film layer is ≤5%.
[0179] In some embodiments, the negative electrode film layer may optionally include other additives. For example, these additives may include thickeners, such as sodium carboxymethyl cellulose (CMC), PTC thermistor materials, and the like. In some embodiments, the weight percentage of these other additives is ≤ 2% based on the total weight of the negative electrode film layer.
[0180] In some embodiments, the negative electrode current collector may be a metal foil or a composite current collector. As an example of a metal foil, copper foil may be used. The composite current collector may include a polymer material base layer and a metal material layer formed on at least one surface of the polymer material base layer. As an example, the metal material may include at least one of copper, a copper alloy, nickel, a nickel alloy, titanium, a titanium alloy, silver, and a silver alloy. As an example, the polymer material base layer may include at least one of polypropylene (PP), polyethylene terephthalate (PET), polybutylene terephthalate (PBT), polystyrene (PS), and polyethylene (PE).
[0181] The negative electrode film layer is typically formed by coating a negative electrode slurry onto a negative electrode current collector, drying, and cold pressing. The negative electrode slurry is typically formed by dispersing the negative electrode active material, an optional conductive agent, an optional binder, and other optional additives in a solvent and stirring until uniformly mixed. The solvent may be, but is not limited to, N-methylpyrrolidone (NMP) or deionized water.
[0182] The negative electrode plate does not exclude other additional functional layers in addition to the negative electrode film layer. For example, in some embodiments, the negative electrode plate described in the embodiments of the present application further includes a conductive primer layer (e.g., composed of a conductive agent and a binder) sandwiched between the negative electrode current collector and the negative electrode film layer and disposed on the surface of the negative electrode current collector. In other embodiments, the negative electrode plate described in the embodiments of the present application further includes a protective layer covering the surface of the negative electrode film layer.
[0183] [Electrolyte]
[0184] During the charge and discharge process of a secondary battery, active ions are embedded and released back and forth between the positive and negative electrodes, and the electrolyte conducts the active ions between the positive and negative electrodes. The present application embodiment does not specifically limit the type of electrolyte, and the electrolyte can be selected based on actual needs.
[0185] The electrolyte solution includes an electrolyte salt and a solvent. The types of the electrolyte salt and the solvent are not particularly limited and can be selected according to actual needs.
[0186] When the secondary battery of an embodiment of the present application is a lithium ion battery, as an example, the electrolyte salt may include, but is not limited to, at least one of lithium hexafluorophosphate (LiPF6), lithium tetrafluoroborate (LiBF4), lithium perchlorate (LiClO4), lithium hexafluoroarsenate (LiAsF6), lithium bisfluorosulfonyl imide (LiFSI), lithium bistrifluoromethanesulfonyl imide (LiTFSI), lithium trifluoromethanesulfonate (LiTFS), lithium difluorooxalatoborate (LiDFOB), lithium dioxalatoborate (LiBOB), lithium difluorophosphate (LiPO2F2), lithium difluorobisoxalatophosphate (LiDFOP) and lithium tetrafluorooxalatophosphate (LiTFOP).
[0187] When the secondary battery of an embodiment of the present application is a sodium ion battery, as an example, the electrolyte salt may include but is not limited to at least one of sodium hexafluorophosphate (NaPF6), sodium tetrafluoroborate (NaBF4), sodium perchlorate (NaClO4), sodium hexafluoroarsenate (NaAsF6), sodium bisfluorosulfonyl imide (NaFSI), sodium bistrifluoromethanesulfonyl imide (NaTFSI), sodium trifluoromethanesulfonate (NaTFS), sodium difluorooxalatoborate (NaDFOB), sodium dioxalatoborate (NaBOB), sodium difluorophosphate (NaPO2F2), sodium difluorobisoxalatophosphate (NaDFOP) and sodium tetrafluorooxalatophosphate (NaTFOP).
[0188] As an example, the solvent may include, but is not limited to, at least one of ethylene carbonate (EC), propylene carbonate (PC), ethyl methyl carbonate (EMC), diethyl carbonate (DEC), dimethyl carbonate (DMC), dipropyl carbonate (DPC), methyl propyl carbonate (MPC), ethyl propyl carbonate (EPC), butylene carbonate (BC), fluoroethylene carbonate (FEC), methyl formate (MF), methyl acetate (MA), ethyl acetate (EA), propyl acetate (PA), methyl propionate (MP), ethyl propionate (EP), propyl propionate (PP), methyl butyrate (MB), ethyl butyrate (EB), 1,4-butyrolactone (GBL), sulfolane (SF), dimethyl sulfone (MSM), ethyl methyl sulfone (EMS) and diethyl sulfone (ESE).
[0189] In some embodiments, the electrolyte may optionally include additives. For example, the additives may include negative electrode film-forming additives, positive electrode film-forming additives, or additives that can improve certain battery properties, such as additives that improve battery overcharge performance, additives that improve battery high-temperature performance, and additives that improve battery low-temperature power performance.
[0190] In some embodiments, the positive electrode sheet, the separator, and the negative electrode sheet may be formed into an electrode assembly through a winding process and / or a lamination process.
[0191] In some embodiments, the secondary battery may include an outer packaging that can be used to encapsulate the electrode assembly and the electrolyte.
[0192] In some embodiments, the outer packaging of the secondary battery can be a hard shell, such as a hard plastic shell, an aluminum shell, a steel shell, etc. The outer packaging of the secondary battery can also be a soft package, such as a bag-type soft package. The material of the soft package can be plastic, such as at least one of polypropylene (PP), polybutylene terephthalate (PBT), and polybutylene succinate (PBS).
[0193] The embodiment of the present application has no particular limitation on the shape of the secondary battery, which can be cylindrical, square, or any other shape. FIG1 shows a secondary battery 5 with a square structure as an example.
[0194] In some embodiments, as shown in FIG2 , the outer packaging may include a shell 51 and a cover plate 53. The shell 51 may include a bottom plate and a side plate connected to the bottom plate, and the bottom plate and the side plate enclose a receiving cavity. The shell 51 has an opening connected to the receiving cavity, and the cover plate 53 is used to cover the opening to close the receiving cavity. The positive electrode sheet, the negative electrode sheet and the isolation film can be formed into an electrode assembly 52 through a winding process and / or a lamination process. The electrode assembly 52 is encapsulated in the receiving cavity. The electrolyte is impregnated in the electrode assembly 52. The number of electrode assemblies 52 contained in the secondary battery 5 can be one or more, which can be adjusted according to demand.
[0195] The preparation methods of the secondary batteries of the embodiments of the present application are well known. In some embodiments, a positive electrode sheet, a separator, a negative electrode sheet, and an electrolyte can be assembled to form a secondary battery. As an example, the positive electrode sheet, separator, and negative electrode sheet can be formed into an electrode assembly through a winding process and / or a lamination process. The electrode assembly is placed in an outer packaging, dried, and then injected with electrolyte. The secondary battery is obtained through vacuum packaging, static standing, formation, and shaping processes.
[0196] In some embodiments of the present application, the secondary batteries according to the present application can be assembled into a battery module. The battery module can contain multiple secondary batteries, and the specific number can be adjusted according to the application and capacity of the battery module.
[0197] Figure 3 is a schematic diagram of an exemplary battery module 4. As shown in Figure 3 , within the battery module 4, multiple secondary batteries 5 may be arranged sequentially along the length of the battery module 4. Of course, any other arrangement is also possible. Furthermore, the multiple secondary batteries 5 may be secured together using fasteners.
[0198] Optionally, the battery module 4 may further include a housing having a receiving space, and the plurality of secondary batteries 5 are received in the receiving space.
[0199] In some embodiments, the battery modules described above may also be assembled into a battery pack, and the number of battery modules contained in the battery pack may be adjusted according to the application and capacity of the battery pack.
[0200] Figures 4 and 5 are schematic diagrams of an exemplary battery pack 1. As shown in Figures 4 and 5, the battery pack 1 may include a battery box and multiple battery modules 4 disposed within the battery box. The battery box comprises an upper case 2 and a lower case 3. The upper case 2 covers the lower case 3 and forms an enclosed space for accommodating the battery modules 4. The multiple battery modules 4 can be arranged in any manner within the battery box.
[0201] In the embodiment of the present application, the battery includes one or more secondary batteries. When the battery includes a plurality of secondary batteries, the battery may include a battery module or a battery pack.
[0202] Electrical devices
[0203] The fourth aspect of the embodiments of the present application provides an electric device, which includes at least one of the secondary battery, battery module or battery pack of the embodiments of the present application. The secondary battery, battery module or battery pack can be used as a power source for the electric device, and can also be used as an energy storage unit for the electric device. The electric device can be, but is not limited to, a mobile device (such as a mobile phone, a laptop computer, etc.), an electric vehicle (such as a pure electric vehicle, a hybrid electric vehicle, a plug-in hybrid electric vehicle, an electric bicycle, an electric scooter, an electric golf cart, an electric truck, etc.), an electric train, a ship and a satellite, an energy storage system, etc.
[0204] The electrical device may select a secondary battery, a battery module or a battery pack according to its usage requirements.
[0205] Figure 6 is a schematic diagram of an exemplary electric device. This device is a pure electric vehicle, a hybrid electric vehicle, or a plug-in hybrid electric vehicle. To meet the high power and high energy density requirements of this device, a battery pack or battery module may be used.
[0206] As another example, the electric device may be a mobile phone, a tablet computer, a laptop computer, etc. Such an electric device is usually required to be lightweight and thin, and may use a secondary battery as a power source.
[0207] Example
[0208] The following examples describe the disclosure of the present invention in more detail. These examples are intended for illustrative purposes only, as various modifications and variations within the scope of the disclosure of the present invention will be apparent to those skilled in the art. Unless otherwise stated, all parts, percentages, and ratios reported in the following examples are by mass, and all reagents used in the examples are commercially available or synthesized according to conventional methods and can be used directly without further processing, and the instruments used in the examples are commercially available.
[0209] Example 1
[0210] Preparation of secondary batteries
[0211] Preparation of isolation membrane
[0212] A first porous base film is provided: a PE base film with a thickness of 5 μm, a porosity of 35%, and an ion conductivity of 1.05 mS / cm.
[0213] A second porous base membrane is provided: a PP base membrane with a thickness of 7 μm, a porosity of 40%, and an ion conductivity of 1.20 mS / cm.
[0214] Preparation of coating slurry: Halloysite nanotubes and aqueous polyacrylic acid binder were mixed in a suitable amount of deionized water at a mass ratio of 95:5 (the mass percentage of halloysite nanotubes B was 95%) to obtain a coating slurry. The volume distribution particle size Dv50 of the halloysite nanotubes was 1.0 μm, the tube thickness H was 3 nm, the tube length L was 0.20 μm, the average pore size D0 of the halloysite nanotubes was 20 nm, the porosity P was 50%, and the specific surface area S was 80 m 2 / g.
[0215] The coating slurry was applied to a PE base film using a coating machine to form a coating layer. The PP and PE base films were then heat-pressed together so that the coating layer was located between the PP and PE base films, thereby forming a separator. The coating layer had a thickness W1 of 2.0 μm and a weight percent of halloysite nanotubes in the coating layer of 95%.
[0216] Preparation of positive electrode
[0217] Aluminum foil was used as the positive electrode current collector.
[0218] The positive electrode active material LiNi 0.8 Co 0.1 Mn 0.1 O2 (NCM811), conductive agent carbon black (Super P), and binder polyvinylidene fluoride (PVDF) are mixed evenly in an appropriate amount of solvent N-methylpyrrolidone (NMP) in a mass ratio of 96.2:2.7:1.1 to obtain a positive electrode slurry; the positive electrode slurry is coated on the positive electrode current collector aluminum foil, and the positive electrode sheet is obtained through drying, cold pressing, slitting, cutting and other processes.
[0219] Preparation of negative electrode sheet
[0220] Copper foil was used as the negative electrode current collector.
[0221] The negative electrode slurry is prepared by mixing artificial graphite (the negative electrode active material), conductive agent Super P, thickener CMC, and binder styrene-butadiene rubber (SBR) in deionized water at a mass ratio of 96:1:1:2. The negative electrode slurry is then coated onto the current collector copper foil. The negative electrode sheet is then obtained through drying, cold pressing, slitting, and cutting.
[0222] Preparation of electrolyte
[0223] In an environment with a water content of less than 10 ppm, the non-aqueous organic solvents ethylene carbonate EC and diethyl carbonate DMC are mixed in a volume ratio of 1:1 to obtain an electrolyte solvent, and then the lithium salt LiPF6 is mixed with the mixed solvent to prepare an electrolyte with a lithium salt concentration of 1 mol / L.
[0224] Preparation of secondary batteries
[0225] The positive electrode sheet, separator, and negative electrode sheet are stacked and wound in sequence to obtain an electrode assembly; the electrode assembly is placed in an outer package, dried, and then injected with electrolyte. After vacuum packaging, standing, formation, shaping and other processes, a secondary battery is obtained.
[0226] Example 2-1 to Example 2-4
[0227] The secondary battery was prepared in a similar manner to that of Example 1, except that:
[0228] The average pore diameter D0 of the halloysite nanotubes used in Example 2-1 is 10 nm, the porosity P is 30%, and the specific surface area S is 100 m 2 / g.
[0229] The average pore diameter D0 of the halloysite nanotubes used in Example 2-2 is 75 nm, the porosity P is 70%, and the specific surface area S is 70 m 2 / g.
[0230] The average pore diameter D0 of the halloysite nanotubes used in Example 2-3 is 105 nm, the porosity P is 80%, and the specific surface area S is 60 m 2 / g.
[0231] The average pore diameter D0 of the halloysite nanotubes used in Examples 2-4 is 5 nm, the porosity P is 20%, and the specific surface area S is 120 m 2 / g.
[0232] Example 3-1 to Example 3-2
[0233] The secondary battery was prepared in a similar manner to that of Example 1, except that:
[0234] The thickness W1 of the coating layer in Example 3-1 is 0.5 μm.
[0235] The thickness W1 of the coating layer in Example 3-2 is 5.0 μm.
[0236] Example 4-1 to Example 4-2
[0237] The secondary battery was prepared in a similar manner to that of Example 1, except that:
[0238] The coating slurry in Example 4-1 is prepared as follows: halloysite nanotubes, alumina, and a binder aqueous solution type polyacrylic acid are mixed uniformly in a mass ratio of 80:15:5 in an appropriate amount of solvent deionized water to obtain a coating slurry. The size specifications of the halloysite nanotubes are as described in Example 1, the mass percentage B of the halloysite nanotubes is 80%, the volume distribution particle size Dv50 of alumina is 1 μm, the mass percentage A of alumina is 15%, and A / B is 0.1875.
[0239] The coating slurry in Example 4-2 was prepared as follows: IRMOFs (metal organic framework material) and binder aqueous solution type polyacrylic acid were mixed uniformly in a proper amount of solvent deionized water at a mass ratio of 95:5 (the mass percentage content B of IRMOFs was 95%) to obtain a coating slurry.
[0240] Example 5-1 to Example 5-5
[0241] The secondary battery was prepared in a similar manner to that of Example 1, except that:
[0242] The tube thickness H of the halloysite in Example 5-1 is 2 nm, and the tube length L is 0.20 μm.
[0243] The tube thickness H of the halloysite in Example 5-2 is 5 nm, and the tube length L is 0.20 μm.
[0244] The tube thickness H of the halloysite in Example 5-3 is 10 nm, and the tube length L is 0.20 μm.
[0245] The tube thickness H of the halloysite in Example 5-4 is 3 nm, and the tube length L is 0.15 μm.
[0246] The tube thickness H of the halloysite in Example 5-5 is 3 nm, and the tube length L is 0.50 μm.
[0247] Comparative Example 1
[0248] The secondary battery was prepared using a method similar to that of Example 1, except that the preparation parameters of the separator were different. The preparation steps of the separator of Comparative Example 1 were as follows:
[0249] Provide PE base film: thickness 5μm, porosity 35%, ion conductivity 1.05mS / cm.
[0250] Preparation of coating slurry: Halloysite nanotubes and binder aqueous solution type polyacrylic acid are uniformly mixed in an appropriate amount of solvent deionized water at a mass ratio of 95:5 to obtain coating slurry.
[0251] The prepared coating slurry was coated on one surface of a PE substrate using a coating machine, and dried to obtain a coating layer, thereby preparing a separator. The mass percentage B of the halloysite nanotubes in the coating layer was 95%.
[0252] Comparative Example 2
[0253] The secondary battery was prepared using a method similar to that of Example 1, except that the preparation parameters of the separator were different. The preparation steps of the separator of Comparative Example 2 were as follows:
[0254] A first porous base film is provided: a PE base film with a thickness of 5 μm, a porosity of 35%, and an ion conductivity of 1.05 mS / cm.
[0255] A second porous base membrane is provided: a PP base membrane with a thickness of 7 μm, a porosity of 40%, and an ion conductivity of 1.20 mS / cm.
[0256] Prepare the coating slurry: Mix aluminum oxide and aqueous polyacrylic acid (a binder) in a 95:5 mass ratio in an appropriate amount of deionized water to obtain a coating slurry. The aluminum oxide has a volume distribution particle size (Dv50) of 1 μm. The aluminum oxide content (B) in the coating is 95% by mass.
[0257] Preparation of isolation film:
[0258] The coating slurry is applied to the PE base film by a coating machine to form a coating layer, and the PP and PE base films are hot-pressed so that the coating layer is between the PP base film and the PE base film to prepare a separator.
[0259] The relevant parameters of the embodiments and comparative examples are shown in Table 1.
[0260] Test section
[0261] 1. Capacity retention rate test of secondary batteries
[0262] At 25°C, the secondary battery was allowed to stand for 30 minutes, then charged at a constant current of 1.0C to a voltage of 4.2V, further charged at a constant voltage of 4.2V to a current of 0.05C, allowed to stand for 5 minutes, and then discharged at a constant current of 1.0C to a voltage of 2.8V. This is a charge and discharge cycle process. The discharge capacity this time is the first discharge capacity of the battery. The secondary battery was subjected to 1000 cycle charge / discharge tests according to the above method, and the discharge capacity of the secondary battery after the 1000th cycle was recorded.
[0263] Capacity retention rate (%) of the secondary battery after 1000 cycles = (discharge capacity at the 1000th cycle / discharge capacity at the first cycle) × 100%.
[0264] Test results
[0265] The test results are shown in Table 1
[0266] Table 1
[0267] As can be seen from Table 1, Comparative Example 2 uses alumina as a filler, and the liquid absorption capacity of the isolation membrane is poor; compared with Comparative Example 2, the embodiment of the present application can significantly improve the liquid absorption capacity of the isolation membrane and enhance the capacity retention rate of the secondary battery by arranging a filler with a porous structure, such as halloysite nanotubes, between the two layers of porous base membranes.
[0268] Compared with Comparative Example 1, the capacity retention rate of Example 1 is significantly improved. Comparative Example 1 sets a coating containing halloysite nanotubes on the surface of the porous base membrane. The coating has a certain liquid absorption capacity and can improve the liquid absorption and liquid retention capacity of the isolation membrane; however, since the coating is exposed on the surface of the porous base membrane, during the cyclic charge and discharge process of the lithium-ion battery, local areas of the coating may detach from the surface of the porous base membrane, thereby deteriorating the cycle performance of the lithium-ion battery and causing its capacity retention rate to decrease. The embodiment of the present application sets a coating containing halloysite nanotubes between two layers of porous base membranes, which can improve the overall liquid retention capacity of the isolation membrane and improve the stability of the isolation membrane structure, thereby improving the cycle performance of the lithium-ion battery and improving its capacity retention rate.
[0269] Although the present application has been described with reference to preferred embodiments, various modifications may be made thereto and components may be substituted with equivalents without departing from the scope of the present application. In particular, the various technical features described in the various embodiments may be combined in any manner as long as there are no structural conflicts. The present application is not limited to the specific embodiments disclosed herein, but encompasses all technical solutions within the scope of the claims.
Claims
1. A separation film, comprising: a first porous base membrane and a second porous base membrane; A coating layer is disposed between the first porous base membrane and the second porous base membrane, and the coating layer includes a filler having a pore structure.
2. The isolation film according to claim 1, wherein: The average pore size of the pore structure of the filler is recorded as D0, and its unit is nm, and D0≥5; Optionally, 10≤D0≤105.
3. The isolation film according to claim 1 or 2, wherein: The porosity of the filler is denoted as P, 20%≤P≤80%; optionally, 20%≤P≤70%; further optionally, 40%≤P≤70%.
4. The separator according to any one of claims 1 to 3, wherein: The specific surface area of the filler is denoted as S, and its unit is m 2 / g, 40≤S≤150; optionally, 60≤S≤120.
5. The separator according to any one of claims 1 to 4, wherein: The volume distribution particle size Dv50 of the filler is 0.01 μm to 3 μm; optionally 0.05 μm to 2 μm.
6. The separator according to any one of claims 1 to 5, wherein: The filler comprises at least one of a metal-organic framework material and a mineral material; Optionally, the metal-organic framework material includes one or more of a mesh metal-organic framework material, a zeolite imidazolate framework series material, a Lavahill framework series material, a pore-channel framework series material, a layered structure series material, and a zirconium-based three-dimensional microporous framework series material; Optionally, the mineral material includes one or more of halloysite nanotubes, vermiculite, attapulgite, sepiolite, montmorillonite, laponite, kaolinite, diatomaceous earth and hydroxyapatite; further optionally, the mineral material includes a through-hole structure; further optionally, the mineral material includes halloysite nanotubes.
7. The separator according to any one of claims 1 to 6, wherein: The pore structure of the filler includes at least one of a through-pore structure and a three-dimensional pore structure.
8. The separator according to any one of claims 1 to 7, wherein: The filler comprises halloysite nanotubes, the thickness of the halloysite nanotubes is H, the unit is nm, 2≤H≤10; optionally, 2≤H≤5; and / or The length of the halloysite nanotube is L, the unit of which is μm, 0.05≤L≤2.50; optionally, 0.15≤L≤1.
50.
9. The separator according to any one of claims 1 to 8, wherein: The mass percentage of the filler in the coating is greater than or equal to 10% and less than 100%; it can be optionally 30% to 95%.
10. The separator according to any one of claims 1 to 9, wherein: The thickness of the coating is W1, the unit is μm, W1≥0.3; optionally, W1≥0.5; further optionally, 0.5≤W1≤5.
0.
11. The separator according to any one of claims 1 to 10, wherein: The coating also includes a heat-resistant filler; Optionally, The porosity of the heat-resistant filler is less than 15%; further, it may be less than 10%; further, it may be less than 5%; and / or The average pore size of the heat-resistant filler is less than or equal to 0.5 nm; Optionally, the mass percentage of the heat-resistant filler in the coating is recorded as A, and the mass percentage of the filler with a porous structure in the coating is recorded as B, then 0.1≤A / B≤10; Optionally, the mass percentage of the heat-resistant filler in the coating is less than or equal to 85%; Optionally, the heat-resistant filler includes at least one of inorganic particles and organic particles.
12. The separator according to any one of claims 1 to 11, wherein: The coating also includes a binder; Optionally, the binder includes one or more of polyacrylate, acrylic acid, carboxymethyl cellulose, polyvinylidene fluoride-co-trichloroethylene copolymer, polymethyl methacrylate, polyvinyl pyrrolidone, polyvinyl acetate, polyethylene-co-vinyl acetate copolymer, polyethylene oxide, polyarylate, cellulose acetate, cellulose acetate butyrate, cellulose acetate propionate, polyvinylidene fluoride, polyacrylonitrile, polyvinyl alcohol, starch, hydroxypropyl cellulose, regenerated cellulose, tetrafluoroethylene, polyethylene, polypropylene and cyanoethyl pullulan.
13. The separator according to any one of claims 1 to 12, wherein: The melting point of the first porous base membrane is less than or equal to the melting point of the second porous base membrane.
14. The isolation film according to claim 13, wherein: The ratio of the average pore size of the first porous base membrane to the average pore size of the second porous base membrane is greater than 1, and can be selected to be greater than or equal to 1.05; Optionally, The average pore size of the first porous base membrane is 0.1 μm to 2 μm, and more preferably 0.1 μm to 0.5 μm; and / or The average pore size of the second porous base membrane is 0.1 μm to 2 μm, and more preferably 0.1 μm to 0.35 μm.
15. The isolation film according to claim 13 or 14, wherein: The porosity of the first porous base membrane is P1, the porosity of the second porous base membrane is P2, P1 / P2≥1.02; optionally, 1.05≤P1 / P2≤2.
50.
16. The separator according to any one of claims 13 to 15, wherein: The porosity P1 of the first porous base membrane is 30% to 80%, and optionally 35% to 50%; and / or The porosity P2 of the second porous base membrane is 25% to 70%, and can be 35% to 45%.
17. The separator according to any one of claims 13 to 16, wherein: The ratio of the thickness of the first porous base membrane to the thickness of the second porous base membrane is greater than or equal to 1.02, and can be optionally 1.2 to 5.
0.
18. The separator according to any one of claims 13 to 17, wherein: The thickness of the first porous base film is 1 μm to 12 μm; optionally 3 μm to 6 μm; and / or The thickness of the second porous base membrane is 2 μm to 12 μm, and can be optionally 3 μm to 5 μm.
19. The separator according to any one of claims 13 to 17, wherein: The ion conductivity of the first porous base membrane is greater than the ion conductivity of the second porous base membrane; Optionally, the ion conductivity of the first porous base membrane is 0.5 mS / cm to 1.5 mS / cm; optionally 0.7 mS / cm to 1.3 mS / cm; Optionally, the ion conductivity of the second porous base membrane is 0.4 mS / cm to 1.5 mS / cm; optionally, 0.6 mS / cm to 1.3 mS / cm.
20. The separator according to any one of claims 1 to 19, wherein: The isolation film satisfies: The liquid absorption rate of the isolation film is 80% to 180%, and can be optionally 100% to 170%. 21 . A secondary battery comprising the separator according to claim 1 .
22. An electric device comprising the secondary battery according to claim 21.
Citation Information
Cited By
Lithium supplementing coating and preparation method thereof, diaphragm and battery
CN120237378A
A lithium supplement coating, a preparation method thereof, a diaphragm and a battery
CN120237378B
Battery diaphragm and lithium ion battery
CN121642436A